The effect of addition of untreated and oxygen plasma treated polypropylene fibers on some properties of heat cured acrylic resin - Waffaa I Mohammed; Intisar J Ismail (College of Dentistry/ University of Baghdad, 2013)
Background: The polymethyl methacrylate is the most reliable material for the construction of complete and partial dentures, despite satisfying esthetic demand itsuffered from having unsatisfactory properties like impact strength and transverse strength. This study was designed to improve the impact strength and transverse strength of heat cure acrylic resin by adding untreated and oxygen plasma treated polypropylene fibers and investigate the effect of this additive on some properties of acrylic resin materials. Materials and methods: Untreated and oxygen plasma treated polypropylene fibers was added to PMMA powder by weight 2.5 %. Specimens were constructed and divided into 5 groups according to the using tests; each group was subdivided in to 3 subgroups. The tests conducted were impact strength, transverse strength, surface hardness, surface roughness, water sorption and solubility. Data were analyzed by one way analysis of variance (ANOVA) and least significant differences (LSD). Results: After incorporation of untreated and oxygen plasma treated polypropylene fibers there was a highly significant increase in impact strength and surface hardness; while there was a non significant difference in transverse strength. Also the value of water sorption increase significantly but with the limit of ADA specification. Conclusion:Within the limit of this study it can be concluded that the reinforcement with polypropylene fibers effective method to increase fracture resistance of denture base; while reinforcement with oxygen plasma treated polypropylene fibers further increase fracture resistance.